Mental health care - Hungerford, Catherine (John Wiley & Sons, Australia, 2018)
This text introduces health professionals to the specialty field of mental health, and describes how mental health services are delivered in Australia today. The text provides a useful resource for health professionals who work in general health settings and also for students of the health professions. It gives an overview of the core skills and knowledge required by health professionals to support people who are affected by mental illness, regardless of where they live in Australia.